STUDI KOMPARATIF KUALITAS PELAYANAN PERIZINAN DALAM JARINGA DAN LUAR JARINGAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PADANG - Ningsih Ardila Sari; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to provide an analysis of the comparison of the quality of licensing services for the online system and the manual system at the Department of Investment and One Stop Services (DPMPTSP) in Padang City. In thit study using qualitative research methodswith purposive sampling technique. Sources of data used in this study include primary data and secondary data, with data collection techniques carried out through observation, interviews and documentation. the location of the research was carried out at the Department of Investment and One Stop Integrated Service, Padang City. The theory used to analyze in this study is ServQual Alanezi et al theory which consists of 6 dimensions of reliability, responsiveness, security / privacy, customization, information, and Ease of use (ease of use). From the results of this study it is known that, the quality of licensing services at DPMPTSP Padang City with the offline system is better than the online system service, therefore people still choose to come directly to DPMPTSP Padang City to get licensing service directly because it is considered easier and clear. Licensing using the online system is deemed not able to fully answer the needs of the community, one of the reasons is the too long process of having to register through two applications, and the time for issuing permits which is still the same as the Offline system. So that there is no significant difference in the online and offline licensing process.  Keywords: licensing, service quality, online system, manual system.